The Critical Role of Long Noncoding RNA in Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells. (27th April 2017) - Qiu, Xiaoling; Jia, Bo; Sun, Xiang; Hu, Weitao; Chu, Hongxing; Xu, Shuaimei; Zhao, JianJiang
Abstract : Objective . Long noncoding RNAs (lncRNAs) have been demonstrated to regulate many biological processes including differentiation. However, their role in osteogenic differentiation was poorly known. Materials and Methods . In this study, we first globally profiled the differentially expressed lncRNAs and mRNAs during osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMMSCs). Bioinformatics analysis was performed to further analyze these significantly changed molecules. Then the role of lncRNA ENST00000502125.2 in the osteogenic differentiation was determined. Results . A number of lncRNAs and mRNAs were significantly differentially expressed during hBMMSC osteogenic differentiation. Among them, 433 lncRNAs and 956 mRNAs were continuously upregulated, while 232 lncRNAs and 229 mRNAs were continuously downregulated. Gene Ontology and KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis showed that carbohydrate derivative binding and complement and coagulation cascades were most correlated molecular function and pathway, respectively. Downregulation of lncRNA ENST00000502125.2 promoted the osteogenic differentiation of hBMMSCs, and opposite results were found when lncRNA ENST00000502125.2 was upregulated. Conclusions . lncRNAs play a critical role in the osteogenic differentiation of hBMMSCs and targeting lncRNA ENST00000502125.2 might be a promising strategy to promote osteogenic differentiation.